Higher-order cladding mode excitation of femtosecond-laser-inscribed tilted FBGs - Ioannou, Andreas; Theodosiou, Antreas; Kalli, Kyriacos; Caucheteur, Christophe (My University, 2018)
We study the modal behavior of plane-by-plane femtosecond laser fabricated tilted fiber Bragg gratings (FBGs). The focus is on the differential strain and temperature sensitivities between the cladding mode resonances of an nth grating order and those of the (n - i)th orders (with i = 1 - n), which are collocated in the same wavelength range. Whereas the Bragg mode exhibits an axial strain sensitivity of 1.2 pm/µε, we experimentally show that the strain sensitivity of ultrahigh-order cladding modes is negative and at -1.99 pm/µe in the same spectral window. Using a finite element mode solver, the modal refractive index value is computed to be well below 1, thus confirming that these modes, in reality, are leaky modes.
Keywords: Femtosecond lasers; Fiber Bragg gratings; Refractive index; Cladding mode excitations; Cladding mode resonances; Differential strain; Finite element modes; Modal refractive indices; Strain sensitivity; Temperature sensitivity; Tilted fiber Bragg grating; Laser excitation